Genomic analyses reveal selection footprints in rice landraces grown under on‐farm conservation conditions during a short‐term period of domestication. (30th September 2019) - Cui, Di; Lu, Hongfeng; Tang, Cuifeng; Li, Jinmei; A, Xinxiang; Yu, Tengqiong; Ma, Xiaoding; Zhang, Enlai; Wang, Yanjie; Cao, Guilan; Xu, Furong; Qiao, Yongli; et al.
Abstract: Traditional rice landraces grown under on‐farm conservation conditions by indigenous farmers are extremely important for future crop improvement. However, little is known about how the natural selection and agriculture practices of indigenous farmers interact to shape and change the population genetics of rice landraces grown under on‐farm conservation conditions during the domestication. In this study, we sequenced DNA from 108 core on‐farm conserved rice landraces collected from the ethnic minority regions of Yunnan, China, including 56 accessions collected in 1980 and 52 accessions collected in 2007 and obtained 2, 771, 245 of credible SNPs. Our findings show that most genetic diversity was retained during the 27 years of domestication by on‐farm conservation. However, SNPs with marked allele frequency differences were found in some genome regions, particularly enriched in genic regions, indicating changes in genic regions may have played a much more prominent role in the short‐term domestication of 27 years. We identified 186 and 183 potential selective‐sweep regions in the indica and japonica genomes, respectively. We propose that on‐farm conserved rice landraces during the short‐term domestication had a highly polygenic basis with many loci responding to selection rather than a few loci with critical changes in response to selection. Moreover, loci affecting important agronomic traits and biotic or abiotic stress responses have been particularly targeted in selection. A genome‐wide association study identified 90 significant signals for six traits, 13 of which were in regions of selective sweeps. Moreover, we observed a number of significant and interesting associations between loci and environmental factors, which implies adaptation to local environment. Our results provide insights into short‐term evolutionary processes and shed light on the underlying mechanisms of on‐farm conservation.